Effects of Gastric Neuromodulation on Crohn's Disease in Patients With Coexisting Symptoms of Gastroparesis. Issue 8 (18th February 2020) - Bhatti, Sundus; Jaafar, Imad; Hassan, Hamza; Atassi, Hadi; Stocker, Abigail; Hughes, Michael; Pinkston, Christina; Dryden, Gerald; Abell, Thomas
Abstract : Introduction: Crohn's Disease (CD) results from chronic inflammation of the gastrointestinal (GI) tract involving TNF‐α release. Gastrointestinal electrical stimulation (GES), a form of neuromodulation used to treat upper GI motility symptoms (UGI Sx), exerts an anti‐inflammatory effect via TNF‐α suppression. We hypothesized patients with CD symptoms in patients with gastroparesis (GP) may respond to GES. Methods: We retrospectively examined 284 patients with symptomatic gastroparesis (Gp Sx), who underwent GES placement. Patients with Gp Sx were evaluated by validated GI Sx patient reported outcome. Scores were obtained at baseline, after temporary GES placement and after permanent GES placement. Eleven patients from this cohort with coexisting CD were analyzed for improvements in their CD symptomatology using the Harvey Bradshaw Index (HBI). HBI scores were compared from before GES to after two sequential applications of electrical stimulation (temporary then permanent). A 3‐point decrease in HBI indicated a clinical response and an HBI <5 indicated clinical remission after GES. An unadjusted repeated measures model was used in the analysis with statistical significance set at p  ≤ 0.05. Results: Our cohort prevalence of CD was 3.9% (2 M & 9 F, mean age 49.8 yrs.). Within both the Gp + CD & Gp subgroups, UGI Sx substantially improved after temporary and permanent GES. Furthermore, 55% of the GP + CD subgroup demonstrated a clinical response by HBI, while one patient achieved clinical remission ( p  < 0.01). CD medications were reviewed before and after GES placement, and any interval changes are unlikely to explain the improved HBI scores. Discussion: We conclude that both UGI and CD symptoms in GP + CD patients responded well to GES. The interaction of Gp and CD and the effects of neuromodulation on CD symptoms warrant additional investigation.